Comparison of Transcutaneous Electric Nerve Stimulation (TENS) and Microcurrent Nerve Stimulation (MENS) in the Management of Masticatory Muscle Pain: A Comparative Study - B. Saranya; Junaid Ahmed; Nandita Shenoy; Ravikiran Ongole; Nanditha Sujir; Srikant Natarajan (Pain Research and Management)
Introduction. Temporomandibular disorders (TMDs) are a heterogeneous group of pathologies affecting the temporomandibular joint (TMJ), the jaw muscles, or both. Epidemiological studies of TMD reveal a prevalence of 82% in the general population with 48% of them presenting with clinical features of muscle tenderness and difficulty in mouth opening. TMD are considered to be the most common orofacial pain conditions of nondental origin. Methods. The patients with TMD were randomly divided into two groups, A and B, based on their VAS scale. Group A consists of two subgroups 1 and 2 each consisting of 15 patients. Group B consists of two subgroups 3 and 4 consisting of 15 patients. Patients in Group A were given TENS for twenty minutes, and the frequency is adjusted as follows: (i) subgroup 1: TENS frequency at a range of 0–5 (VAS measuring 1–5) and (ii) subgroup 2: TENS frequency at a range of 5 and above (VAS measuring 6–10). Patients in Group B were given MENS for twenty minutes, and the frequency adjusted as follows: (i) subgroup 3: MENS frequency at range of 0–5 (VAS measuring 1–5) and (ii) subgroup 4: MENS frequency at a range of 5 and above (VAS measuring 6–10). Each patient was recalled for five consecutive days for the treatment, and the same intensity and frequency were maintained throughout the treatment period. Results. The improvement in VAS is seen to be highly significant statistically in MENS subgroup 4 (moderate-to-severe pain). Subgroups 1 and 3 had improvement in VAS which was comparable in both TENS and MENS groups. Conclusion. In the present study, it was found that TENS and MENS are equally effective in improving the functional mouth opening. MENS showed better and immediate effect in relief of pain. Microcurrent also has the advantage of being subthreshold, and hence the side effects such as tingling sensation and paresthesia seen to occur in some patients following TENS are absent. TENS and MENS can be considered as the first line of treatment in patients with acute and chronic masticatory muscle pain and also as an effective treatment option in cases of functional mouth opening.